Impact of "Sambhav" Program (Financial Assistance and Counselor Services) on Hepatitis C Pegylated Interferon Alpha Treatment Initiation in India - Ajit Sood; Vandana Midha; Shivalingappa S. Halli; Vikram Narang; Ramit Mahajan; Varun Mehta; Kirandeep Kaur; Vijay Surlikar; Subodh Kanchi; Dharmatma Singh (Kerman University of Medical Sciences, 2018)
Background Financial constraints, social taboos and beliefs in alternative medicine are common reasons for delaying or not considering treatment for hepatitis C in India. The present study was planned to analyze the impact of non-banking interest free loan facility in patients affected with hepatitis C virus (HCV) in North India. Methods This one year observational, retrospective study was conducted in Department of Gastroenterology (January 2012-December 2013), Dayanand Medical College and Hospital Ludhiana, to evaluate the impact of program titled "Sambhav" (which provided non-banking financial assistance and counselor services) on treatment initiation and therapeutic compliance in HCV patients. Data of fully evaluated patients with chronic hepatitis, and/or cirrhosis due to HCV infection who were treated with Peginterferon alfa and ribavirin (RBV) combination during this duration (2012-2013) was collected from patient medical records and analyzed. In the year 2012, eligible patients who were offered antiviral treatment paid for treatment themselves, while in 2013, 'Sambhav' program was launched and this provided interest free financing by non-banking financial company (NBFC) for the treatment of HCV in addition to free counselor services for disease management. The treatment initiation and compliance rates were compared between the patients (n = 585) enrolled in 2013 who were offered 'Sambhav' assistance and those enrolled in 2012 (n = 628) when 'Sambhav' was not available. Results Introduction of Sambhav program improved the rates of treatment initiation (59% in 2013 vs. 51% in 2012, P = .004). Of the 585 eligible patients offered 'Sambhav' assistance in 2013, 233 patients (39.8%) applied but 106/233 (45.4%) received assistance. Antiviral therapy was started in 93/106 (87.7%) of these patients, while only 52 (42.5%) of 127 patients whose applications were rejected underwent treatment. Compliance to antiviral therapy also improved with the introduction of 'Sambhav' program (87.7% vs. 74.1%, P = .001). Conclusion 'Sambhav' program had significant impact on the initiation of antiviral therapy by overcoming the financial hurdles. The free counselor services helped to mitigate social taboos and imparted adequate awareness about the disease to the patients. Initiatives like 'Sambhav' can be utilized for improving healthcare services in developing countries, especially for chronic diseases.